ASPECTUAL USE OF ADA IN PAPUAN MALAY - Onisimus Faot, (Journal of Innovation Research and Knowledge, 2025)
This paper presents an analysis on compatibilities and constraints of aspectual verb ada ‘exist’ with lexical semantic verb types in Papuan Malay. The data used here were collected from different sources especially jokes in Papuan Malay from internet, examples from Kluge (2017) and Morin (2018), and some stories from three language consultants. These were collected as part of the first corresponding author’s Master thesis research. The results of the study show that the word ada may be used to denote three senses. First, it is used as a main verb which could either be copula used initially before NP followed by PrepP, or, second, as main verb expressing ownership whose subject is the possessor and predicative noun the possessum. Third, ada ‘exist’ is used as an aspectual verb which is the topic of this paper. When ada is used as an aspect, it is more compatible with dynamic verbs comprising activity, achievement, accomplishment and semelfactive rather than stative verbs. Issues that remain to be seen are all aspectual verbs and their syntactic and semantic behaviors in relation to lexical verb types in Papuan Malay.